Pap smear prevalence and that of pre-malignant and malignant cervical lesions amongst women living in the Carmen initiative demonstration area, Bucaramanga, Colombia Prevalencia de uso de citología vaginal y de lesiones premalignas y malignas del cérvix entre las mujeres del área demostrativa Carmen, Bucaramanga, Colombia - Claudia Janeth Uribe-Pérez; Luis Alfonso Díaz-Martínez; Ricardo Ortiz-Serrano; Erika Eliana Meza-Durán (Federación Colombiana de Obstetricia y Ginecología, 2006)
Objective: Establishing the prevalence of premalignant and malignant cervical lesions amongst women living in the CARMEN initiative demonstration area, Bucaramanga, Colombia. Methodology: A cross-sectional study of 8,015 randomly selected women. Patients having abnormal cytology results received individualised diagnosis/treatment (colposcopy, biopsy, or conisation). Histopathological findings were correlated with demographical data and their sexual and reproductive history. Results: 8,071 women answered the survey but only 2,698 had up-to-date Pap smears (34.9%; 95%CI 17.2%-29.8%); 1,660 accepted updating their smears. 2.2% (95%CI 1.8%-2.6%) had Pap smears positive for cervical lesions, this being higher in those living with more mature women. Pre-malignant and malignant cervical lesion prevalence was 1.1% (95%CI 0.8%-1.4%). Women with pre-malignant or malignant cervical lesions were younger, had begun their sexual intercourse earlier and had had more sexual partners than healthy women. Conclusions: Pre-malignant and malignant cervical lesion prevalence is higher than in other parts of the world. Pap smear coverage is very low. Early detection of cervical cancer must be intensified. Objetivo: Establecer la prevalencia de lesiones premalignas y malignas entre las mujeres que viven en el área demostrativa de la iniciativa CARMEN de Bucaramanga, Colombia. Metodología: Estudio trasversal de 8.015 mujeres seleccionadas al azar. Las pacientes con citología anormal fueron estudiadas y tratadas de manera individualizada según un protocolo que incluía colposcopia, biopsia o conización. Se hizo correlación histopatológica con las variables sociodemográficas y la historia sexual y reproductiva Resultados: 8.071 mujeres contestaron la encuesta, pero solo 2.698 tenía una citología reciente (34,9%; IC 95% 17,2%-29,8%); 1.660 actualizaron su citología. 2,2% de estas fueron positivas, siendo más alta entre las mujeres que viven con otras mujeres adultas. La prevalencia de lesiones premalignas y malignas del cuello uterino fue 1,1% (IC 95% 0,8%-1,4%). Las mujeres con lesiones cervicales premalignas o malignas eran más jóvenes, habían iniciado relaciones sexuales más temprano y habían tenido más compañeros sexuales que las mujeres sanas. Conclusiones: La prevalencia de lesiones cervicales premalignas y malignas es superior a la que se informa en otras partes del mundo, mientras que la cobertura de citología cérvicovaginal es muy baja. Es necesario intensificar las actividades que buscan la detección temprana de cáncer cervical.